Adeline Hagaman and past SJSU presidents. - Unknown:::Creator::::::::::::
Written on verso: "9/22/1978; Adeline with Presidents. Four SJSU presidents turned out with 146 other faculty and staff to pay Tribute to Adeline Hagaman, retiring Sept. 29 after 35-years at SJSU. With Mrs. Hagaman (center) are (l to r) Hobart Burns, Gail Fullerton, John Wahlquist and John Bunzel."